Pharmacokinetics, safety, and efficacy of Fuqi Guben Gao in the treatment of kidney-yang deficiency syndrome: a randomized, double-blind phase I trial - Cao, Wei-Yi; Liu, Jun-Yu; Sun, Min; Wang, Jing-Kun; Lu, Fang; Yang, Qiao-Ning; Zhang, Wan-Tong; Zi, Ming-Jie; Zhang, Bai-E; Liu, Hong-Bin; Wang, Shu-Ge; Wu, Yi; et al. (Frontiers in Pharmacology, 2024)
Introduction: Fuqi Guben Gao (FQGBG) is a botanical drug formulation composed of FuZi (FZ; Aconitum carmichaelii Debeaux [Ranunculaceae; Aconiti radix cocta]), Wolfberry (Lycium barbarum L. [Solanaceae; Lycii fructus]), and Cinnamon (Neolitsea cassia (L.) Kosterm. [Lauraceae; Cinnamomi cortex]). It has been used to clinically treat nocturia caused by kidney-yang deficiency syndrome (KYDS) for over 30 years and warms kidney yang. However, the pharmacological mechanism and the safety of FQGBG in humans require further exploration and evaluation. Methods: We investigated the efficacy of FQGBG in reducing urination and improving immune organ damage in two kinds of KYDS model rats (hydrocortisone-induced model and natural aging model), and evaluated the safety of different oral FQGBG doses through pharmacokinetic (PK) parameters, metabonomics, and occurrence of adverse reactions in healthy Chinese participants in a randomized, double-blind, placebo-controlled, single ascending dose clinical trial. Forty-two participants were allocated to six cohorts with FQGBG doses of 12.5, 25, 50, 75, 100, and 125 g. The PKs of FQGBG in plasma were determined using a fully validated LC-MS/MS method. Results: FQGBG significantly and rapidly improved the symptoms of increased urination in both two KYDS model rats and significantly resisted the adrenal atrophy in hydrocortisone-induced KYDS model rats. No apparent increase in adverse events was observed with dose escalation. Major adverse drug reactions included toothache, thirst, heat sensation, gum pain, diarrhea, abdominal distension, T-wave changes, and elevated creatinine levels. The PK results showed a higher exposure level of benzoylhypaconine (BHA) than benzoylmesaconine (BMA) and a shorter half-life of BMA than BHA. Toxic diester alkaloids, aconitine, mesaconitine, and hypaconitine were below the lower quantitative limit. Drug-induced metabolite markers primarily included lysophosphatidylcholines, fatty acids, phenylalanine, and arginine metabolites; no safety-related metabolite changes were observed. Conclusion: Under the investigated dosing regimen, FQGBG was safe. The efficacy mechanism of FQGBG in treating nocturia caused by KYDS may be related to the improvement of the hypothalamus-pituitary-adrenal axis function and increased energy metabolism. Clinical Trial Registration:https://www.chictr.org.cn/showproj.html?proj=26934, identifier ChiCTR1800015840.